PERANAN PROGRAM DESA PRIMA TERHADAP KEMANDIRIAN EKONOMI PEREMPUAN DI KALURAHAN SUMBERRAHAYU KAPANEWON MOYUDAN KABUPATEN SLEMAN - Nurrohmah, Annida; Khozin, Muhammad (SULTAN ADAM: Jurnal Hukum dan Sosial, 2024)
The women's empowerment program launched by the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia is called the DESA PRIMA (Advanced Independent Indonesian Women) program which has the aim of realizing women who advance independently in the economic field. Several things that are inhibiting factors in the progress of prime villages in Sumberrahayu Village can be used as strong reasons for this research to be carried out, including the lack of assistance in prime villages and the age factor of their administrators. This is interesting to research so that we know the role of prime villages in efforts to realize women's economic independence. In the process, this research aims to determine the level of success of the prime village program for women's economic independence in Sumberrahayu District and the factors that influence it using Hutomo's (2000) theory. The approach used in the empowerment program includes rolling capital assistance, infrastructure development assistance, institutional strengthening, strengthening business partnerships, and mentoring assistance. This research is qualitative research using a descriptive approach. The data collection techniques used were observation, interviews and documentation. The results of this research show that capital assistance was provided without continuity and received other assistance from special funds at the end of 2022. Institutional strengthening in the prime village has not yet been implemented. There will be no assistance for the construction of infrastructure until 2022. Strengthening business partnerships is built only within the internal members of the prime village. Mentoring assistance is felt to be lacking. The level of success of the prime village program for women's economic independence in Sumberrahayu District cannot be said to be successful.